Reseña/Review (Ragnedda, Massimo, "The third digital divide: a Weberian approach to digital inequalities" Nueva York: Routledge, ISBN: 9781472471260 (hbk); ISBN: 978131560600 (ebk), 128 págs., 2017) - Calderón Gómez, Daniel (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2018)
Reseña/Review (Ragnedda, Massimo, "The third digital divide: a Weberian approach to digital inequalities" Nueva York: Routledge, ISBN: 9781472471260 (hbk); ISBN: 978131560600 (ebk), 128 págs., 2017)